Perancangan dan Pembuatan Dapur Peleburan Logam dengan Menggunakan Bahan Bakar Gas (LPG) - Amir Zaki Mubarak; - Akhyar (Jurnal Teknik Mesin Unsyiah, 2013)
Foundry industry is very important in the development of both machinery and household products. Furnace is important utility in producing a product. Available furnaces in the market are very costly and difficult to obtain due to be imported from abroad. Responding these issues, in this study is designed and developed a furnace that is simple, easy to manufacture, portable and most importantly the price is low so that it is affordable for industrial-scale domestic foundry industry. The furnace is heated with LPG (Liquefied Petroleum Gas) as the gas is economical and obtainable. Refractory stones are used as a heat insulator to increase the temperature in the combustion chamber to reach 1,000 oC. The heat can be set via the setting of gas that goes into the combustion chamber so that it can be adapted for different types of material with a melting temperature below 1,000 oC. The type of metal melted in this research is aluminum. The test results showed that the furnace is able to melt 0.39 kg of aluminum in 30.15 minutes.